2021
DOI: 10.1177/10870547211063641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Youth With ADHD: Predictors and Moderators of Response to Pandemic Restrictions on Daily Life

Abstract: We examined COVID-19 symptoms and infection rates, disruptions to functioning, and moderators of pandemic response for 620 youth with ADHD and 614 individually matched controls (70% male; Mage = 12.4) participating in the Adolescent Brain and Cognitive Development study. There were no group differences in COVID-19 infection rate; however, youth with ADHD were more likely to exhibit COVID-19 symptoms ( d = 0.25), greater sleep problems ( d = −0.52), fear and negative emotions to infection risk ( d = −0.56), tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…COVID-19 infection status did not significantly differ among patients and controls which was not in line with some studies ( 2 , 3 ) but corroborated with others ( 7 ). The discrepancy may firstly be explained by differences in the timing of the studies.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…COVID-19 infection status did not significantly differ among patients and controls which was not in line with some studies ( 2 , 3 ) but corroborated with others ( 7 ). The discrepancy may firstly be explained by differences in the timing of the studies.…”
Section: Discussionsupporting
confidence: 45%
“…Our findings are consistent with a study in children where researchers showed that children with ADHD were not more likely to experience COVID-19 infection. This study followed a similar methodology to ours and demonstrated the COVID-19 rate among ADHD and controls ( 7 ). Another study exhibited no correlations between ADHD and population size infection and mortality rates from coronavirus.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent papers suggest that youth/adults with ADHD are less like to wash their hands, use hand sanitizer, maintain social distance, and more likely to engage in rule-breaking behaviors related to COVID-19 restrictions ( Conway et al, 2022 ; Rosenthal et al, 2022 ). Rosenthal and colleagues (2021) theorize that individuals with ADHD, due to their inattention and hyperactivity/impulsivity, may be more likely to put themselves in high-risk situations as it relates to health safety measures (e.g., not socially distancing).…”
Section: Introductionmentioning
confidence: 99%